Inflation Risk in Corporate Bonds - KANG, JOHNNY; PFLUEGER, CAROLIN E. (Journal of Finance, 2015)
ABSTRACT We argue that corporate bond yields reflect fears of debt deflation. When debt is nominal, unexpectedly low inflation increases real liabilities and default risk. In a real business cycle model with optimal but infrequent capital structure choice, more uncertain or procyclical inflation leads to quantitatively important increases in corporate log yields in excess of default‐free log yields. A panel of credit spread indexes from six developed countries shows that credit spreads rise by 14 basis points if inflation volatility or the inflation‐stock correlation increases by one standard deviation.